Calcium fortification of tomato jam - Orcena, Joanne Felissa C.; Francisco, Ma. Leonora dL. (2002)
ABSTRACT Prevalence of micronutrient in the Philippines, particularly calcium had been the main interest of this study. Calcium is a very important mineral needed to promote growth and development of the bones. It plays a key role in fighting a disease known as osteoporosis, which is common to women especially the elderly. Children are of great need of calcium to prepare their body for later years in life. The main objective of this study is to fortify a locally produced tomato jam with the most acceptable form and level of calcium salt. Phase I dealt with the determination of the physico-chemical properties and calcium content of the unfortified tomato jam. The standardized formulation of tomato jam was adopted from Dia (2000). Samples from the production were obtained and subjected to physico-chemical tests and calcium content analysis. Calcium content of the unfortified tomato jam was found to be 7.17 mg Ca/100 g using Atomic Absorption Spectrophotometry (AAS). Phase II focused on the determination of the most acceptable calcium salt and the level of the calcium salt to be added. The amount of calcium salt added to the tomato jam was based on 1/3 RDA for calcium for children aged 7-9. Consumer Acceptability Test and ANOVA showed that the most acceptable calcium salt was calcium triphosphate with an overall acceptability of 5.52. Varying levels of calcium triphosphate was then incorporated in the tomato jam to determine the optimum level for the jam. Results of Consumer Acceptability Test showed that the tomato jam with 33.33% calcium was the most acceptable among all formulations, having an acceptability of 6.60. Phase III entailed the standardization of the calcium fortification of the tomato jam in terms of the physicochemical, microbiological, sensory evaluation and calcium content analysis. Two production runs of calcium fortified tomato jam were produced and found to have no significant difference in all attributes. The samples were found to have the following attributes: pH-3.83; %titratable acidity-0.65; soluble solids-68.29; water activity-0.73; color-5 YR 7/10; Yeast and Mold Count (YMC)- <10 cfu/g; and calcium content-197.01 mg/10 g tomato jam.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Jam; Jam, Enriched